A chromosome-scale genome assembly of the leaf roller, Eumorphobotys obscuralis (Lepidoptera: Pyralidae) - Shu-Zhen Wang; Jun-Ran Zhao; Yu-Mei Dong; Wei Zhang; Yue Ying; Jin-Ping Shu; Jin-Ming Zhang; Peng-Jun Zhang (Scientific Data, 2025)
Abstract The leaf roller, Eumorphobotys obscuralis, is a highly destructive pest that causes severe defoliation, ultimately reducing plant vigor, leading to culm death, and resulting in significant economic and ecological losses. Despite its substantial impact, effective prevention and control strategies remain lacking, further exacerbating the damage caused by this species. To address the critical gap in genomic resources, we generated a high-quality chromosome-scale genome assembly for E. obscuralis using a combination of Illumina short reads, PacBio HiFi long reads, and Hi-C chromatin interaction data. The final assembly spans 701.9 Mb across 31 chromosomes, including the single sex chromosome Z. Key assembly metrics include a contig N50 of 1.73 Mb and a scaffold N50 of 23.70 Mb, with an estimated genome completeness of 96.7%. Genome annotation identified 15,855 protein-coding genes and revealed that repetitive sequences account for 58.9% of the genome. This genomic resource lays a solid foundation for exploring the genetic mechanisms underlying the pest’s biology and adaptation, and serves as a valuable reference for the development of targeted pest management strategies.